Attitude towards heterosexual premarital sexual behaviors and some psychosocial family factors a case of female first year college students from a co-educational school. - Jaranilla, Lydia Dawn Deocades; Pachoco, Ayn Fritzi Chavez (2004.)
The study sought to demonstrate the attitude of female first year college students towards heterosexual premarital sexual behaviors and its relationship to some psychosocial family factors, family openness of communication, perceived authoritative parental control, and family modeling. The study was conducted to the 50 female first year college students of College of Arts and Sciences, UPV. Design of this study was descriptive-correlational. Scales were used to measure the variables in this study. These were the Attitude towards Sexual Behavior Scale (ASBS) and Family Modeling of Sexual Behavior Scale (FMSBS), which the researchers made; the modified Parent-Adolescent Communication-Jaccard (PACJ) and Parental Authority Questionnaire (PAQ). Data were analyzed using the Spearman Rank Order Correlation. Analysis showed that general attitude towards heterosexual premarital sexual behavior of UPV-CAS female first year students was related to family modeling. However, there were no significant correlations between the general attitude towards heterosexual premarital sexual behaviors and family openness of communication and perceived authoritative parental control. Looking into the dimensions of the attitude towards heterosexual premarital sexual behaviors, it was found that family openness of communication was positively correlated to some dimensions of the attitude towards heterosexual premarital sexual behaviors. The correlation between the attitude towards heterosexual premarital sexual behaviors and family modeling was discussed in term of Social Learning Theory. The implications of the per dimension analysis were also discussed.
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2004.
Keywords: Heterosexual premarital sexual behaviors -- Female -- Research; College students -- female -- Research